Seroprevalence of Antibodies to SARS-CoV-2, at Four Sites in Al-Jabal Al Akhdar, Libya - Faraj Sulayman; Marfoua S. Ali; Salema Qowaider (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and aims. SARS CoV-2 is a global pandemic that has affected all aspects of life. The implementation of strategies to mitigate possible cases of SARS CoV-2 has become particularly important in controlling the spread of the pandemic. Such studies are lacking in Libya. The objectives of this study were to determine the presence of anti-SARS-CoV-2 antibodies in random populations in four different regions in Northeast of Libya (El-Beyda, Shahat, Al-Gubba and Al-Abraq). Methods. This study included all 1567 samples from November 1-14, 2020. A total of 1567 tested cases of SARS-CoV-2 were recorded in four regions with men (63.9%) and women (36.1%). Ages ranged between 9 and 84 years. The median age of the tested individuals was 35-36 years for both genders. Results. Over all, the number of cases was higher at age groups 20-60 years in four regions. Overall subjects, serological tests to detect anti SARS-CoV-2 antibodies were found positive for (IgG, IgM) with (57, 46%), (24.4, 2.9%), (95.4, 91.7%) and (60.9, 51.9%) in El-Beyda, Al-Gubba, Al-Abraq and Sahhat respectively. Over all, the number of positive IgG cases was higher at age groups 20-50 years in four regions with significant difference only in Al-Abraq region. Broad geographic variability and spatiotemporal spread variation of the SARS-CoV-2 pandemic in Libya was observed, indicating a significant increase of SARS-CoV-2 spread starting in the middle of July 2020. Conclusion. Detection of SARS-CoV-2 in the early stages of the epidemic is particularly important in understanding the pandemic spread. Such assessments are essential for designing effective prevention and control programs aimed at reducing the impact of the SARS CoV-2 pandemic, particularly in countries with limited resources.